Infliximab is a plausible alternative for neurologic complications of Behçet disease. Issue 5 (October 2016) - Zeydan, Burcu; Uygunoglu, Ugur; Saip, Sabahattin; Demirci, Onat N.; Seyahi, Emire; Ugurlu, Serdal; Hamuryudan, Vedat; Siva, Aksel; Kantarci, Orhun H.
Abstract : Objective: We evaluated the effectiveness of infliximab in patients with neuro-Behçet syndrome for whom other immunosuppressive medications had failed. Methods: Patients whose common immunosuppressive medications fail in recurrent neuro-Behçet syndrome need an alternative. We report our experience with the tumor necrosis factor α blocker infliximab for long-term treatment of neuro-Behçet syndrome. We recruited patients within a multidisciplinary referral practice of Behçet disease and prospectively followed everyone with a neurologic symptom(s). Patients (n = 16) with ≥2 neurologic bouts (excluding purely progressive disease) while on another immunosuppressive treatment were switched to and successfully sustained on infliximab (5 mg/kg in weeks 0, 2, and 6, then once every 8 weeks; minimum follow-up duration ≥12 months). Infliximab was stopped within 2 months after initiation in one patient because of pulmonary and CNS tuberculosis. Results: Patients had stepwise worsening due to relapses in the Expanded Disability Status Scale modified for neuro-Behçet syndrome before switching to infliximab (median score of 5.0, range 2.0–7.0; median neuro-Behçet syndrome duration 29.1 months, range 5.0–180.7). Median duration of preinfliximab immunosuppressive medication use was 20.0 months (range 3.0–180.7). In all 15 patients, during infliximab treatment (median score 4.0, range 2.0–7.0; median duration 39.0 months, range 16.0–104.9 months), neurologic relapses were completely aborted and there was no further disability accumulation. Conclusion: We observed a significant beneficial effect of infliximab in neuro-Behçet syndrome. Classification of evidence: This study provides Class IV evidence that for patients with neuro-Behçet syndrome whose other immunosuppressive medications failed, infliximab prevents further relapses and stabilizes disability.